Leisure and alienation in Houellebecq's fiction. (November 2021) - Willging, Jennifer
This article examines representations of leisure in Michel Houellebecq's fiction. Theorised as a new human need that arose from the alienating nature of work in industrial society, leisure is one of three sectors of everyday life explored by modern sociologists. Marxist philosopher and sociologist Henri Lefebvre saw in leisure a domain in which human beings could experience moments of freedom and fulfilment, but which was becoming increasingly controlled and commercialised and therefore as potentially alienating as work. This article argues that Houellebecq's fiction portrays contemporary leisure activities, such as shopping, tourism, physical exercise, smoking, and television-watching, as manifestations of this latter kind of leisure, which has proliferated under neoliberalism. His protagonists attempt, if often half-heartedly, to compensate for neoliberalism's erosion of family and work as stabilising forces to find identity and fulfilment in leisure. If their efforts inevitably fail, Houellebecq's attention to everyday leisure at least confirms Lefebvre's contention that a critical evaluation of leisure was increasingly urgent.